THE DEVELOPMENT OF POP UP BOX LEARNING MEDIA ACCORDING TO CONSTRUCTIVISM THEORY AT ISLAMIC JUNIOR HIGH SCHOOL - Mukaromah, Muhimmatul; Sholikhah, Ika Yulia Kurniatus (Abjadia : International Journal of Education, 2025)
This study aims to explain the development process of the pop up box media, and analyze the validity, practicality, and effectiveness of pop up box media developed to improve the learning outcomes of students in Islamic Junior High School Hudatulmuna 2. This type of research is Research and Development by taking steps from the ADDIE development model. Samples in this study are students in Class 7A and 7B a number of each 13 children. Aspects that are validated by the validator are material aspects and media aspects. The practicality of pop up box media is known by providing response questionnaires to learners. The effectiveness of pop up box media is known by providing tests to learners. The results of this study are: 1) The development process of pop up box media is carried out through 5 stages, namely the analysis stage, design stage, development stage, implementation stage, and evaluation stage. 2) The pop up box is declared very valid shown from the results of the validity of the material and the media that got an average percentage of 85.8%. The pop up box is stated to be very practical shown from the positive response of students who obtained a percentage of 93%. The pop up box declared quite effective is shown from the results of the N-Gain test of 59.52%. It can be concluded that pop up box Learning media has been tested to be valid, practical and effective in improving learners learning outcomes.